Clinical Reasoning: An unusual cause of indeterminate spells. (6th December 2016) - Feyissa, Anteneh M.; Kenney-Jung, Daniel L.; Shin, Cheolsu; Cheville, John C.; So, Elson L.
Abstract : A 38-year-old, right-handed woman presented to the epilepsy clinic for evaluation of recurrent spells. These spells are characterized by an aura of a "rushing" cephalic sensation and a sense of "spaciness" or "dizziness" followed by loss of awareness with subsequent amnesia for the event. During these events, the patient is observed by family to sit down and slump forward or fall, followed by hyperventilation and occasionally staring, for up to 3 minutes. There is no head turn, eye deviation, or abnormal body movements. Postictally, she reports generalized weakness without focality and confusion. The spells occurred sporadically for 8 years, but recently increased in frequency to 5 to 20 times per day. Triggers included lack of sleep, stress, and various food products. The patient reported some improvement with levetiracetam therapy at 1, 500 mg twice daily.